PERAN COGNITIVE EMOTION REGULATION STRATEGIES TERHADAP INTOLERANCE OF UNCERTAINTY PADA EMERGING ADULTHOOD DITINJAU DARI PERBEDAAN GENDER - Evelyn Jolyn Angmulya; Agustina Agustina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Uncertainty is an essential part of an individual's life, especially during the emerging adulthood phase, which is characterized by various developmental transitions. An individual's inability to tolerate uncertainty or intolerance of uncertainty is known to contribute to the occurrence of emotional responses and maladaptive behaviors. One of the psychological factors that influences how individuals cope with uncertainty is cognitive emotion regulation strategies, which are cognitive strategies used by individuals to manage emotional responses to stressful situations. This study aimed to examine the role of cognitive emotion regulation strategies in intolerance of uncertainty among emerging adulthood based on gender differences. The study used a non-experimental quantitative approach with purposive sampling of 303 participants aged 18 to 25 years. The instruments used were the Cognitive Emotion Regulation Questionnaire (CERQ) and the Intolerance of Uncertainty Scale-12 (IUS-12). The results showed that cognitive emotion regulation strategies played a significant role in intolerance of uncertainty, contributing 41.4%. Adaptive cognitive emotion regulation strategies had a negative effect on intolerance of uncertainty, while maladaptive cognitive emotion regulation strategies had a positive effect. Furthermore, findings revealed differences in the use of cognitive emotion regulation strategies based on gender, with women exhibiting higher scores for adaptive and maladaptive strategies compared to men. Nevertheless, no differences were discovered in the level of intolerance of uncertainty between men and women. ABSTRAK Ketidakpastian merupakan bagian yang tidak terpisahkan dari kehidupan individu, terutama pada fase emerging adulthood yang ditandai oleh berbagai transisi perkembangan. Ketidakmampuan individu dalam mentoleransi ketidakpastian atau intolerance of uncertainty diketahui berkontribusi terhadap munculnya respons emosional dan perilaku maladaptif. Salah satu faktor psikologis yang berperan dalam menghadapi ketidakpastian adalah cognitive emotion regulation strategies, yaitu strategi kognitif yang digunakan individu untuk mengelola respons emosional terhadap situasi yang menimbulkan stres. Penelitian ini bertujuan untuk menguji peran cognitive emotion regulation strategies terhadap intolerance of uncertainty pada emerging adulthood ditinjau berdasarkan perbedaan gender. Penelitian menggunakan pendekatan kuantitatif non-eksperimental dengan teknik purposive sampling terhadap 303 individu berusia 18 hingga 25 tahun. Instrumen penelitian meliputi Cognitive Emotion Regulation Questionnaire (CERQ) dan Intolerance of Uncertainty Scale-12 (IUS-12). Hasil penelitian menunjukkan bahwa cognitive emotion regulation strategies berperan signifikan terhadap intolerance of uncertainty dengan kontribusi sebesar 41,4%. Strategi regulasi emosi kognitif adaptif berpengaruh negatif terhadap intolerance of uncertainty, sedangkan strategi regulasi emosi kognitif maladaptif berpengaruh positif. Selain itu, ditemukan perbedaan penggunaan cognitive emotion regulation strategies berdasarkan gender, di mana perempuan menunjukkan skor strategi adaptif dan maladaptif yang lebih tinggi dibandingkan laki-laki. Namun, tidak ditemukan perbedaan tingkat intolerance of uncertainty antara laki-laki dan perempuan.